2004
DOI: 10.1158/1078-0432.ccr-0911-3
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy and Lung Cancer Risk

Abstract: Purpose: To date, there are few published data regarding the use of hormone replacement therapy (HRT) and lung cancer risk. Therefore, we analyzed data regarding HRT use from a large case-control study designed to study genetic susceptibility to lung cancer to determine whether HRT affected risk of lung cancer.Experimental Design: In a secondary analysis, we compared self-reported HRT use among 499 women with lung cancer and 519 healthy age-matched controls.Results: HRT use was associated with an overall reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
129
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 78 publications
3
129
3
1
Order By: Relevance
“…25 Olsson et al demonstrated a reduced lung cancer risk in HRT ever users; long-term HRT use (48 months) was associated with a reduced risk of smoking-related cancers, including lung cancer. 26 Schabath et al 27 found HRT use within the previous 6 months was associated with a reduced lung cancer risk. In our study, we defined HRT use as ever use of HRT for 3 months or more, which is similar to the definition by Blackman et al 23 The association of HRT and reduced lung cancer risk could be found in studies with different durations of HRT use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Olsson et al demonstrated a reduced lung cancer risk in HRT ever users; long-term HRT use (48 months) was associated with a reduced risk of smoking-related cancers, including lung cancer. 26 Schabath et al 27 found HRT use within the previous 6 months was associated with a reduced lung cancer risk. In our study, we defined HRT use as ever use of HRT for 3 months or more, which is similar to the definition by Blackman et al 23 The association of HRT and reduced lung cancer risk could be found in studies with different durations of HRT use.…”
Section: Discussionmentioning
confidence: 99%
“…24 Conversely, several studies have demonstrated an inverse association between HRT use and lung cancer risk. [25][26][27] Because of the high female to male ratio of lung cancer patients in Taiwan and the frequent use of HRT in women for postmenopausal symptoms, the hypothesis that HRT may be associated with reduced lung cancer risk is of clinical importance and needs confirmation. In this study, we investigated whether HRT was associated with a reduced lung cancer risk in Chinese women.…”
mentioning
confidence: 99%
“…Eleven studies have reported on the association of HRT and risk of lung cancer. 18,19,21,22,[24][25][26]28,30,31,35 Most of these studies do not define whether their results pertain to estrogen alone or estrogen plus progestin. One early cohort study from Sweden, 19 which assessed exposure to both potent estrogens and weaker Each factor is adjusted for all other factors, including for parity (4 levels), age at menarche (4 levels), menopausal status (pre-, peri-and postmenopausal), oral contraceptive use (ever/never), hormone replacement use (ever/never), body mass index (continuous), education (3 categories), smoking status (never, former smoker and current smoker), pack-years of smoking (continuous), study center and randomization group (intervention versus control).-2 Among parous women.…”
Section: Discussionmentioning
confidence: 99%
“…A second cohort study from Sweden, 25 24 However, follow-up of this cohort was rather short (mean of 5.2 years). Of the remaining studies, in which the specific type of preparation was not defined, 2 studies reported statistically significant reductions in risk 28,35 ; one reported a nonsignificant reduction in risk 31 ; and 3 reported nonsignificant or borderline increases in risk. 18,21,30 Our result indicating that 10 years of HRT use is associated with modestly increased risk needs to be confirmed in other prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this finding was an effect of chance, confounders, a tumourrelated effect, or another cancer-related effect is unclear. Although estrogen replacement therapy has not shown a consistent effect on lung cancer incidence (and may even be slightly protective 13 ), the possible association of estrogen replacement therapy with an aggressive course of lung cancer was highly interesting.…”
Section: Introductionmentioning
confidence: 99%